Managerial cognition and internationalization - Maitland, Elizabeth; Sammartino, André (Journal of International Business Studies, 2015)
How do the senior decision-makers within a multinational enterprise (MNE) think through and determine an internationalization decision? Despite the cognitive foundations of several key constructs, standard internationalization models do not explicitly incorporate managerial cognition. We argue that the boundedly rational decision-maker is underspecified in international business models and this oversight contributes to weak empirical findings on experience, learning, internationalization strategy and MNE performance. Drawing on these extant models, we identify seven knowledge domains and interdependencies that may make up decision-makers’ mental models. Granted rare access to senior executives and board members engaged in a foreign direct investment decision, we find substantial heterogeneity in the mental models these individuals used to make sense of the opportunity. This variance aligns with differences in individuals’ experience along four dimensions: international breadth, depth, diversity and prior strategic decision-making. We argue these cognitive processes – how individuals exercise judgment about information search parameters, assessment and decision integration, and how decision teams coalesce in their thinking – are crucial microfoundations for modeling heterogeneity in firm-level internationalization strategies and performance.